1995
DOI: 10.1111/j.1432-1033.1995.tb20866.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Stable BHK-21 Cells Coexpressing Human Secretory Glycoproteins and Human Gal(beta1-4)GlcNAc-R alpha2,6-Sialyltransferase. alpha2,6-Linked NeuAc is Preferentially Attached to the Gal(beta1-4)GlcNAc(beta1-2)Man(alpha1-3)-Branch of Diantennary Oligosaccharides from Secreted Recombinant beta-Trace Protein

Abstract: FEBS 1995 Construction of stable BHK-21 cells coexpressing human secretory glycoproteins and human Gal@-4)GlcNAc-R ~2,6-~ialyltransferase cr2,6-Linked NeuAc is preferentially attached to the Gal(pl-4)GlciVAc(pl-2)Man(crl-3)-branch of diantennary oligosaccharides from secreted recombinant /3-trace protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…On account of the small quantity of OvGST1b and the minute differences between both proteins observed, only two specific glycopeptides of OvGST1b were identified. Glycopeptide 1, consisting of amino acids 4 to 18 (GP1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] ) of OvGST1b, could not be detected and analyzed (Table 1). On all four glycosylation sites of OvGST1a, molecular ions with mass increments of 162 Da were detected, suggesting the presence of high-mannose type structures differing Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On account of the small quantity of OvGST1b and the minute differences between both proteins observed, only two specific glycopeptides of OvGST1b were identified. Glycopeptide 1, consisting of amino acids 4 to 18 (GP1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] ) of OvGST1b, could not be detected and analyzed (Table 1). On all four glycosylation sites of OvGST1a, molecular ions with mass increments of 162 Da were detected, suggesting the presence of high-mannose type structures differing Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the analyte mixture was 1 to 10 pmol/l. Determination of the molecular masses was carried out by positive-ion MALDI-TOF MS using a Bruker REFLEX time-of-flight instrument as described by Grabenhorst et al (15).…”
Section: Maldi-tof Msmentioning
confidence: 99%
“…Genetic augmentation of sialyltransferase activity in mammalian cells has not consistently increased the total sialic acid content of glycoproteins. Although Weikert et al (1999) demonstrated that overexpression of ␣2,3-sialyltransferase in CHO cells resulted in increased glycoprotein sialylation (>90% of branches), expression of ␣2,6-sialyltransferase in BHK-21 cells had no such effect, although ␣2,6-linked sialic acids were present (Grabenhorst et al, 1995).…”
Section: Effect Of N-acetylmannosamine On Cell Growth and N-glycosylamentioning
confidence: 96%
“…In addition to the identification of tyrosine sulfate residues detected with the ESI technique, we were also able to identify the dominant glycoforms of all three potential glycopeptides [NLSMPLLPADFHK (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), DFVNASSK(166-173), SMTNR(T) (365-370)] after desialylation by mild acid hydrolysis ( Table 1). As the corresponding unmodified peptides were neither detectable by MALDI nor by ESI-MS, we deduce from these results that all three potential HCII N-glycosylation sites are completely glycosylated.…”
Section: R E S U L T S Expression Of Hcii From Cho Cellsmentioning
confidence: 99%
“…Approximately 60% of the triantennary structures isolated from the serum HCII contained a fucose residue. In order to determine the linkage position of the fucose to the triantennary structure, ESI-MS/MS analysis was performed on the triply charged molecular ion [M + 3Na] 3+ after isolation of the trisialylated oligosaccharide fraction by anion exchange chromatography on a Mono Q column [31]. From the resulting daughter ion spectrum (Fig.…”
Section: Detailed Characterization Of the N-glycans From Serum And Chmentioning
confidence: 99%